On the mean value of the function S_k(n) - Varbanets, P. D.; Kirbat, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
An asymptotic formula is constructed for a mean value of the function S_k(n) which is dual to the Smarandache function S_k(n). O- and Ω-estimates for the second moment of the remainder term are obtained.